The Effect of Smart Apps Creator on Improving Student History Learning Outcomes - Oka Agus Kurniawan Shavab (Universitas Pendidikan Ganesha, 2025)
Students have low learning outcomes because the media and sources of history learning are not varied. This study aimed to determine how effective the use of Smart Apps Creator learning media is in improving students' history learning outcomes. The research method used was a quasi-experimental study with a population of 423 students from class X of high school. The research sample was divided into two groups, 35 in the experimental and 32 in the control classes, selected using purposive sampling techniques. The data collection process used a validated multiple-choice test. The data collected through the pretest-posttest was processed by finding the n-gain of the data. Furthermore, the Man Whitney U Test analysis was carried out. The results showed that Smart Apss Creator and PowerPoint students had better history learning outcomes. The Mann Whitney U hypothesis test value at the Asymptotic Sig. (2-sided test) is 0.000 <0.05. In addition, the average N-Gain of 69.25% indicates that the Smart Apps Creator learning media is quite effective in improving students' history learning outcomes. Using Smart Apps Creator is quite effective in improving student learning outcomes. The study for teachers implies that using Smart Apps Creator as a learning medium can be integrated into a learning model or method that suits students to maximize its benefits.